Analisis Faktor-Faktor Yang Memengaruhi Adopsi Digital Banking: Systematic Literatur Review - Nesya Azrina Fernanda Shalvianita; Ardhea Mareta Aini; Ida Ayu Nuh Kartini (CV. SINAR HOWUHOWU, 2026)
The rapid development of information technology has transformed the banking industry through the implementation of digital banking services, which aim to improve efficiency, accessibility, and service quality for customers. Although the use of digital banking continues to increase, its adoption is influenced by various factors that determine customers' willingness to use these services. This study aims to identify the factors influencing digital banking adoption by applying the Systematic Literature Review (SLR) method. The study was conducted by collecting, selecting, and analyzing relevant scientific articles based on predetermined inclusion and exclusion criteria. The findings indicate that perceived usefulness, perceived ease of use, trust, security, social influence, and digital literacy are the primary factors affecting digital banking adoption. In addition, the results reveal that the successful implementation of digital banking depends not only on technological innovation but also on the banking industry's ability to establish customer trust, ensure transaction security, and improve digital literacy. Therefore, banking institutions should continuously enhance service quality, strengthen security systems, and promote digital literacy programs to encourage broader adoption of digital banking services. This study is expected to provide valuable insights for banking practitioners and serve as a reference for future research on digital banking adoption.